Lessons Learned Piloting an EMI Support Course at a Southern Brazilian University - Pusey, Kerry (BELT - Brazilian English Language Teaching Journal, 2020)
While the literature on English as a medium of instruction (EMI) has seen steady growth over the last two decades, the topic of pre- and in-service teacher education for EMI has received relatively little attention—a situation that is even more marked within the context of Brazilian higher education. Responding to this gap with a practice-oriented contribution, this paper distills some of the major insights gained from piloting an EMI support course at a private university in the south of Brazil. The paper is organized around five themes, or ‘lessons learned,’ which represent the most salient takeaways from the piloting experience. These lessons intersect with some of the most pressing issues faced by researchers, practitioners, and policymakers involved with EMI in higher education contexts. By aligning theoretical and practical concerns, the paper seeks to establish an agenda for further investigation into EMI teacher education—especially within the Brazilian context.